Learning Curriculum for Dance at Sayu Wiwit Art Studio in Banyuwangi - Candra Anggraini, Estu; Yanuartuti, Setyo (Jurnal Seni Tari, 2024)
The curriculum is a guideline for implementing learning in the world of education, both formal and non-formal education. Non-formal education has an important role as a complement to formal education. It’s for supporting, strengthening, and developing the learning process, especially in empowering the skills practice of children or students at the institution. An example of non-formal education is a training institution which in the arts field can be called an art studio. Moreover, Banyuwangi is known for its diverse cultures and preservation of traditional arts, one of which is through optimizing art studios, which in this research analyzes the Sayu Wiwit art studio. This research aims to describe and analyze more deeply the planning and implementation of the dance learning curriculum at the Sayu Wiwit art studio. The methods used in collecting data are observation, interviews, and documentation. Analyze the data by reducing, presenting the data, and drawing conclusions. The results of the research show that the dance learning curriculum at the Sayu Wiwit art studio is complex, from the planning to implementation stages. At the planning stage, there are objectives, curriculum content, learning activities, learning resources, and learning evaluation. As for the implementation stage, it is also complete, starting from various types of learning methods, arranging training schedules, management, various studio activity programs, and communication with student parents, to complete facilities and infrastructure owned by the Sayu Wiwit Banyuwangi art studio